The Role of the Concierge in the Front Office Department at the Swiss-Belinn Hotel Jalan Surabaya Medan - Irfan, Muhammad (Healing : Jurnal Pariwisata, 2023)
Concierge is a part of the Front Office department which has an important role in improving quality and service. Such as information, handling goods, welcoming at the hotel gate, searching for guests at the hotel, parking vehicles, transportation out of the hotel, right up to pick-up and drop-off at the airport. To obtain more accurate data, the author conducted a direct inspection of the object to be studied. The author used qualitative research using observations of 2 Concierge people, 1 Front Office Supervisor, and 12 guests who visited the Swiss-Belinn hotel, Jalan Surabaya, Medan. From the results of discussing the data that has been obtained in the field, the author concludes that the duties and responsibilities of a Concierge are still lacking in terms of serving guests, there is a lack of things in handling guest items and there is a lack of close relationships between each department so that misunderstandings can occur. The advice that the author conveys is the need to pay attention to the Standard Operational Procedures that have been provided by the hotel so that they can be implemented properly, the need to be careful in handling guest items. It is also hoped that relationships between departments will be well established so that hotel operations run well and guests feel satisfied with the hotel's services.